Further Observations on the Effect of Synthetic Thyrotrophin-releasing Hormone in Man. Issue 5755 (24th April 1971) - Ormston, B. J.; Kilborn, J. R.; Garry, R.; Amos, Jacqueline; Hall, Reginald
Abstract : Synthetic thyrotrophin-releasing hormone (TRH) given intravenously in doses of 50 μg or more causes a significant rise in serum thyroid-stimulating hormone (TSH) levels but has no effect on serum growth hormone, plasma luteinizing hormone, or plasma 11-hydroxycorticosteroids under carefully controlled basal conditions. The peak TSH response to intravenous TRH occurs at 20 minutes. The mild and transient side effects, which occur only after intravenous TRH, include nausea, a flushing sensation, a desire to micturate, a peculiar taste, and tightness in the chest. There is considerable variability in response to a given dose of TRH in the same subject on different occasions and in different subjects. Oral administration of TRH in doses of 1 mg and above causes a rise in serum TSH, maximal at two hours, a consistent response being obtained at doses of 20 mg and above. A rise in serum protein-bound iodine (P.B.I.) follows that of TSH, a consistent response being observed at 40-mg doses of TRH orally. Measurements of serum TSH after intravenous administration of TRH or of serum TSH or serum P.B.I. after oral TRH should prove useful tests of pituitary TSH reserve.